Assessment of carotid atherosclerosis, intraplaque neovascularization, and plaque ulceration using quantitative contrast-enhanced ultrasound in asymptomatic patients with diabetes mellitus. (27th June 2014) - van den Oord, Stijn C.H.; Akkus, Zeynettin; Renaud, Guillaume; Bosch, Johan G.; van der Steen, Antonius F.W.; Sijbrands, Eric J.G.; Schinkel, Arend F.L.
Abstract: Aims: Patients with diabetes mellitus (DM) are at severely increased risk of developing atherosclerosis. Intraplaque neovascularization (IPN) and plaque ulceration are markers of the vulnerable plaque, which is at an increased risk of rupture and may lead to cardiovascular events. The aim of this study was to assess the prevalence of subclinical carotid atherosclerosis, intraplaque neovascularization (IPN), and plaque ulceration in asymptomatic patients with DM. Methods and results: A total of 51 asymptomatic patients with DM underwent standard carotid ultrasound in conjunction with contrast-enhanced ultrasound (CEUS) to assess the prevalence of subclinical atherosclerosis, IPN, and plaque ulceration. Subclinical atherosclerosis was defined as the presence of atherosclerotic plaque, according to the Mannheim consensus. Semi-automated quantification software was used to assess IPN in suitable plaques. Plaque ulceration was defined as a disruption of the plaque–lumen border of ≥1 × 1 mm. A total of 408 carotid segments in 102 carotid arteries were investigated. Forty-six (90%) patients had subclinical atherosclerotic plaques, with a median plaque thickness of 2.4 mm (inter-quartile range 1.9–3.0). CEUS revealed IPN in 88% of the patients. In 10 carotid segments (8%), the plaque had an ulcerated surface. The presence of IPN could not be predicted by the presence of clinical characteristics including complications of DM ( P > 0.05). Conclusion: Patients with DM have a high prevalence (90%) of subclinical carotid atherosclerosis. Severe IPN and plaque ulceration, which are markers of the vulnerable plaque type, were detected in, respectively, 13 and 9% of these patients.